THE LITERARY LEGACY OF MARK TWAIN IN SHAPING AMERICAN REALISM AND NATIONAL IDENTITY - Iroda Egamberdiyeva Abdurahimovna; Najimov Dilshodbek Hasanboy o‘g‘li (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article examines the literary legacy of Mark Twain and his significant role in shaping American realism and national identity. The study explores how Twain’s works reflect the social realities of nineteenth-century America through the use of regional language, satire, and realistic characterization. Particular attention is given to his portrayal of everyday life along the Mississippi River and his critique of social injustice, including issues of race, class, and morality. The research highlights Twain’s contribution to the development of a uniquely American literary voice that moved away from European traditions and embraced local culture and experiences. His innovative narrative techniques and emphasis on authenticity helped establish realism as a dominant literary movement in the United States. Furthermore, the article argues that Twain’s works played a crucial role in shaping American national consciousness by presenting diverse perspectives and challenging prevailing social norms.